Putative Roles of SETBP1 Dosage on the SET Oncogene to Affect Brain Development - Antonyan, Lilit; Ernst, Carl (Frontiers in Neuroscience, 2022)
Mutations in SET BINDING PROTEIN 1 (SETBP1) cause two different clinically distinguishable neurodevelopmental diseases called Schinzel-Giedion Syndrome (SGS) or SETBP1 deficiency syndrome (SDD). Both disorders can be seen as disorders of protein dosage, where SGS is caused by decreased rate of protein breakdown due to mutations in a proteosome targeting domain, and SDD is caused by heterozygous loss-of-function mutations leading to haploinsufficiency. While clinical presentations support a role for SETBP1 in brain development, little is known about the mechanisms that might underlie this. The binding partner which gave SETBP1 its name is SET and there is extensive literature on this important oncogene in non-neural tissues. Here we describe different molecular complexes in which SET is involved as well as the role of these complexes in brain development. Based on this information, we postulate how SETBP1 protein dosage might influence different molecular pathways and affect brain development. We examine the inhibitor of acetylation complex, protein phosphatase 2A; DNA repair and chromatin remodeling activity; and cell cycle control in relation to their role with SET and brain development. This work should provide testable hypotheses for how SETBP1 protein dosage alters brain development and may lead to SGS or SDD.